Electrical Properties of a CeO2-Bi2O3 Mix System Elaborated at 600°C - Lamia Bourja; Bahcine Bakiz; Abdeljalil Benlhachemi; Mohamed Ezahri; Sylvie Villain; Claude Favotto; Jean-Raymond Gavarri (Advances in Materials Science and Engineering)
The electrical conduction of a series of polycristalline [(1−x)CeO2⋅x/2Bi2O3] samples has been analyzed using electrical impedance spectroscopy, in the temperature range 25 to 750∘C. Samples have been prepared via a coprecipitation route followed by a pyrolysis process at 600∘C. For compositions x≤0.20, Ce1−xBixO2−x/2 solid solutions, with fluorite cubic structure, are obtained. In the composition range 0.30≤x≤1, the system is biphasic with coexistence of cubic and tetragonal structures. To interpret the Nyquist representations of electrical analyses, various impedance models including constant phase elements and Warburg impedances have been used. In the biphasic range (0.30≤x≤0.7), the conductivity variation might be related to the increasing fraction of two tetragonal β′ and β-Bi2O3 phases. The stabilization of the tetragonal phase coexisting with substituted ceria close to composition x=0.7 is associated with a high conduction of the mix system CeO2-Bi2O3.